El proceso de enseñanza aprendizaje de la oratoria desde la lectura comprensiva en los estudiantes de educación básica media de la Unidad Educativa América de la parroquia Abañin en el periodo lectivo 2013-2014. - Espinoza Narváez, Miriam Patricia (2014)
Reading comprehension lead the person a significantly Learning , a knowing the world, a iterrelacionarse other characters from a literary Enjoy the beauty and foremost to value critically What Others Say . Meanwhile , speaking is a communicative process Aiming At persuade the receivers , the same as that achieved from the UN Writing Argumentative Discourse where they play a series of reading comprehension skills .